PET imaging of 52Mn labeled DOTATATE and DOTAJR11 - James M. Omweri; Hailey A. Houson; Shannon E. Lynch; Volkan Tekin; Anna G. Sorace; Suzanne E. Lapi (Scientific Reports)
Abstract Manganese-52 is gaining interest as an isotope for PET imaging due to its desirable decay and chemical properties for radiopharmaceutical development. Somatostatin receptor 2 (SSTR2) is significantly overexpressed by neuroendocrine tumors (NETs) and is an important target for nuclear imaging and therapy. As an agonist, [68Ga]Ga-DOTATATE has demonstrated significant internalization upon interaction with receptor ligands, whereas [68Ga]Ga-DOTA-JR11(as an antagonist) exhibits limited internalization but better pharmacokinetics and increased tumor uptake. The goal of this study was to label both DOTATATE and DOTA-JR11 peptides with 52Mn in high radiochemical yields (RCY) and sufficient specific activity. A comparison of these two compounds was performed in in vitro and in vivo studies in animals with somatostatin receptor-positive xenografts to characterize differences in cell, tumor, and tissue uptake. Radiolabeling of DOTATATE and DOTA-JR11 was carried out by combining varying concentrations of the peptides with [52Mn]MnCl2. In vitro stability of the radiotracers was determined in mouse serum. In vitro cell uptake and internalization assays were performed in SSTR2 + AR42J cells and negative controls. In vivo biodistribution and longitudinal PET imaging was evaluated in mice bearing AR42J tumors. Both [52Mn]Mn-DOTATATE and [52Mn]Mn-DOTA-JR11 showed affinity for SSTR2 in AR42J cells. However, the uptake of [52Mn]Mn-DOTATATE was higher (11.95 ± 0.71%/ mg) compared to [52Mn]Mn-DOTA-JR11 (7.31 ± 0.38%/ mg) after 2 h incubation. After 4 h incubation, 53.13 ± 1.83% of the total accumulated activity of [52Mn]Mn-DOTATATE was internalized, whereas only 20.85 ± 0.59% of the total accumulated activity of [52Mn]Mn-DOTA-JR11 was internalized. The PET images revealed similar biodistribution results, with [52Mn]Mn-DOTATATE showing a significant tumor uptake of 11.16 ± 2.97% ID/g, while [52Mn]Mn-DOTA-JR11 exhibited a lower tumor uptake of 2.11 ± 0.30% ID/g 4 h post-injection. The synthesis of both radiotracers was accomplished with high RCY and purity. The cell uptake and internalization of [52Mn]Mn-DOTATATE showed higher levels compared to [52Mn]Mn-DOTA-JR11. PET images of the radiotracers in AR42J tumor bearing mice demonstrated similar biodistribution in all organs except the tumor, with [52Mn]Mn-DOTATATE showing higher tumor uptake compared to [52Mn]Mn-DOTA-JR11. The variations in the properties of these tracers could be used to guide further imaging and treatment studies.